Clinical Significance of Early Echocardiographic Changes after Resuscitated Out-of-Hospital Cardiac Arrest. (March 2022) - Sarma, Dhruv; Pareek, Nilesh; Kanyal, Ritesh; Cannata, Antonio; Dworakowski, Rafal; Webb, Ian; Barash, Jemma; Emezu, Gift; Melikian, Narbeh; Hill, Jonathan; Shah, Ajay M.; MacCarthy, Philip; et al.
Abstract: Background: Left Ventricular Systolic Dysfunction (LVSD) is common after out-of-hospital cardiac arrest (OOHCA) and can manifest globally or regionally, although its clinical significance has not been robustly studied. This study evaluates the association between LVSD, extent of coronary artery disease (CAD) and outcome in those undergoing early echocardiography and coronary angiography after OOHCA. Methods: Trans-thoracic echocardiography (TTE) was performed in OOHCA patients on arrival to our centre between May 2012 and December 2017. Rates of cardiogenic shock and extent of CAD, respectively classified by SCAI grade and the SYNTAX score, were measured. The primary end-point was 12-month mortality. Results: From 398 patients in the King's Out of Hospital Cardiac Arrest Registry (KOCAR), 266 patients (median age 61 [53–71], 76% male) underwent both TTE and coronary angiography on arrival. 96 patients (36%) had significant LVSD (Left Ventricular Ejection Fraction [LVEF] <40%) and 139 (52.2%) patients had regional wall motion abnormalities (RWMAs). Patients with LVEF <40% had more SCAI grade C-E shock (65.3% vs. 34.5%, p <0.001) and higher 12-month mortality (55.2% vs 31.8%, p <0.001) which was more likely to be due to a cardiac aetiology (27.3% vs 5.3%, p <0.001). Patients with RWMAs had higher median SYNTAX scores (14.75 vs 7, p=0.001), culprit coronary lesions (83.5% vs. 45.3%, p <0.001) and lower 12-month mortality (29.5% vs 52%, p <0.001). Conclusions: Patients with LVEF <40% at presentation have an increased mortality, driven by cardiac aetiology death, while the presence of RWMAs is associated with a higher rate of culprit coronary lesions, representing a potentially reversible cause of the arrest, and improved survival at 1 year.